Breaking through the silence in antenatal care: Fetal movement and stillbirth education. Issue 1 (February 2020) - Pollock, Danielle; Ziaian, Tahereh; Pearson, Elissa; Cooper, Megan; Warland, Jane
Abstract: Background: Fetal movements are a key indicator of fetal health. Research has established significant correlations between altered fetal activity and stillbirth. However, women are generally unaware of this relationship. Providing pregnant women with information about the importance of fetal movements could improve stillbirth rates. However, there are no consistent fetal movements awareness messages globally for pregnant women. Aims: This study aimed to explore the antenatal care experiences of Australian mothers who had recently had a live birth to determine their knowledge of fetal movements, the nature and source of that information. Methods: An online survey method was used for 428 women who had a live birth and received antenatal care in Australia. Women's knowledge of fetal movements, stillbirth risk, and the sources of this knowledge was explored. Findings: A large proportion of participants (84.6%; n = 362) stated they had been informed by health care professionals of the importance of fetal movements during pregnancy. Open-ended responses indicate that fetal movements messages are often myth based. Awareness that stillbirth occurs was high (95.2%; n = 398), although, 65% (n = 272) were unable to identify the current incidence of stillbirth in Australia. Conclusion: Women who received antenatal care have high-awareness of fetal movements, but the information they received was inconsistent. Participants knew stillbirth occurred but did not generally indicate they had obtained that knowledge from health care professionals. We recommend a consistent approach to fetal movements messaging throughout pregnancy which focuses on stillbirth prevention.